The importance of meteor monitoring networks - da Costa, Matheus Agenor Gomes [UNESP]; de Andrade, Tainá Bueno [UNESP] (My University, 2025)
This paper aims to present a brief discussion on the importance of meteor monitoring networks, with a special focus on how to set up a monitoring network and the type of scientific research that can be developed. The authors highlight specific aspects of meteoritic research with a focus on digital meteor monitoring.
A importância das redes de monitoramento de meteoros
Keywords: meteoritics; meteoros; meteors; meteorítica; Monitoring networks; Redes de monitoramento